Serologic and Urine Diagnostic Tests to Detect Helicobacter pylori Infection in Functional Dyspepsia Patients - Agasjtya Wisjnu Wardhana; Ari Fahrial Syam; Andri Sanityoso; Cleopas Martin Rumende (The Indonesian Society for Digestive Endoscopy, 2016)
Background: Dyspepsia is a collection of symptoms in the forms of discomfort, pain, nausea, vomiting, bloating, and early satiety in the stomach. This condition can be caused by various problems; one of them is Helicobacter pylori infection. Dyspepsia without organic problem is known as functional dyspepsia. H. pylori examination is recommended in functional dyspepsia patients.Method: In this study, we performed a diagnostic test study in dyspepsia patients in Community Health Centre of Koja District, North Jakarta, from February to April 2015. Samples were obtained through consecutive sampling method; 74 patients were included. The data was gathered by distributing questionnaires to patients, performing urea breath test (UBT) examination, serologic test, and urine test using rapid urine test (RAPIRUN). Results: Prevalence of H. pylori infection by using UBT examination reached up to 36.5%; meanwhile serologic and RAPIRUN tests showed positive results in 32.4% and 24.3% patients, respectively. Serologic test has sensitivity of 74% (95% CI: 55-87%), specificity 91% (95% CI: 80-97%), positive predictive value (PPV) 83% (95% CI: 64-93%), and negative predictive value (NPV) 86% (95% CI: 74-93%). Meanwhile, RAPIRUN has sensitivity of 63% (95% CI: 44-78%), specificity 98% (95% CI: 89-100%), PPV 94% (95% CI: 74-99%), and NPV 82% (95% CI: 70-90%).Conclusion: Sensitivity of serologic and RAPIRUN tests are still inadequate to be alternative to UBT examination. However, they have high specificity. Further studies are required with larger sample size and consideration of factors which may influence the results of both tests.